Case Report: Echinocandin-Resistance Candida glabrata FKS Mutants From Patient Following Radical Cystoprostatectomy Due to Muscle-Invasive Bladder Cancer - Szymankiewicz, Maria; Kamecki, Krzysztof; Jarzynka, Sylwia; Koryszewska-Bagińska, Anna; Olędzka, Gabriela; Nowikiewicz, Tomasz (Frontiers in Oncology, 2021)
Invasive Candida glabrata infections are not common complications after radical cystoprostatectomy. Furthermore, resistance to echinocandins arising during the course of a patient’s treatment is rarely recognised. We described a case of development of echinocandins resistance in a patient with muscle-invasive bladder cancer (pT2b N0 M0, high grade) diagnosis, subjected to radical cystoprostatectomy and exposed to echinocandins. A male patient with a previous surgical history after a traffic accident, who was operated on due to bladder cancer, underwent an episode of candidemia and mixed post-operative wound and urinary tract infection caused by C. glabrata and extended spectrum β-lactamase (ESBL)-producing Escherichia coli during hospital treatment. The patient was started on caspofungin. Repeat blood cultures showed clearance of the bloodstream infection; however, infection persisted at the surgical site. Resistance to echinocandins developed within two months from the day of initiation of therapy with caspofungin in the C. glabrata strain obtained from the surgical site. The isolates sequentially obtained during the patient’s treatment demonstrated resistance to echinocandins due to the mutation in hotspot 1 FKS2. Although resistance to echinocandins is relatively rare, it should be considered in oncological patients with increased complexity of treatment and intestinal surgery.